2016
DOI: 10.3928/01477447-20160623-02
|View full text |Cite
|
Sign up to set email alerts
|

Surface Aneurysmal Bone Cyst: Clinical and Imaging Features in 10 New Cases

Abstract: Aneurysmal bone cyst originating from the surface of the bone, either within the cortex or subperiosteally, is an uncommon anatomic subtype. This article reports the clinical and radiologic evaluations and treatment outcomes of 10 patients with surface aneurysmal bone cysts that were surgically treated between 1982 and 2014. Mean age at the time of surgery was 22.4 years (range, 11-44 years). According to Capanna's radiographic evaluation criteria, 6 of the lesions were classified as type V and 4 were classifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…Surface ABCs extend beyond the confines of the outline of the bone and arise within the cortex of the bone or beneath the periosteum, limited by periosteum externally and endosteum internally [64][65][66]. They were initially referred to as parosteal type in the radiographic classification of ABCs [67] and were named subperiosteal giant cell tumor [31] or subperiosteal osteoclasia [32].…”
Section: Surface Abcsmentioning
confidence: 99%
See 4 more Smart Citations
“…Surface ABCs extend beyond the confines of the outline of the bone and arise within the cortex of the bone or beneath the periosteum, limited by periosteum externally and endosteum internally [64][65][66]. They were initially referred to as parosteal type in the radiographic classification of ABCs [67] and were named subperiosteal giant cell tumor [31] or subperiosteal osteoclasia [32].…”
Section: Surface Abcsmentioning
confidence: 99%
“…In the radiographic classification developed by Capanna et al [1,30], surface ABCs were described as types IV and V. According to this classification, type IV lesions include subperiosteal forms that develop away from the bone so that the cortex is either intact or superficially eroded. Type V lesions develop both peripherally toward the periosteum and centrally toward the medulla so that the cortex is penetrated [30,[64][65][66]. Maiya et al [64] described a cortical metaphyseal ABC that showed similar degrees of intraosseous and extraosseous extension and tended to be more aggressive than subperiosteal ABCs.…”
Section: Surface Abcsmentioning
confidence: 99%
See 3 more Smart Citations